2008
DOI: 10.1007/s10597-008-9135-x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceived Barriers to Working with Families of Persons with Severe Mental Illness: Mental Health Professionals’ Perspectives

Abstract: A state-wide survey of 453 clinicians serving people with severe mental illness in community mental health centers evaluated the degree to which they provide services to families and their perceptions of barriers to developing such services. Most clinicians did not provide many services to families and reported barriers related to the family or client (e.g., family's lack of interest) and their own work environment (e.g., heavy workload). Clinicians who had received prior training on working with families prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 39 publications
6
60
1
Order By: Relevance
“…Determining the scope, effectiveness and impact of policies and programs to promote health including the appropriate use of assessment and research methods to support improvement in programs, sustainability and dissemination (15) . Research on the roles of the expanded practice of community mental health nurses indicated that they were less confident about prescribing, even though, more than half (54%) reported that they definitely or Evaluates the coordinated response in development of unplanned care services for mental health (8) Identifies confidence and preparation of community mental health nurses when performing expanded roles (9) Identifies cultural factors that contributed to substance abuse in adolescents (10) Explores how mental health workers and respond to women who reveals sexual abuse in the scenario of crisis service (11) Professionals identify cultural barriers of women in attendance (11) Managing and negotiating health care delivery systems nurse practitioner-patient relationship teaching/coaching Function Analyzes the extent of mental health services provided to families (12) On the significance of the relationship with the patient, highlights the genuine partnership and confidence (13) Unidentified probably felt confident to prescribe medication. More than 90% said they probably or definitely felt confident in making recommendations for involuntary treatment, 84% and 79% showed similar levels of confidence in ordering of diagnostic tests and in referring patients to specialist physicians, respectively (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the scope, effectiveness and impact of policies and programs to promote health including the appropriate use of assessment and research methods to support improvement in programs, sustainability and dissemination (15) . Research on the roles of the expanded practice of community mental health nurses indicated that they were less confident about prescribing, even though, more than half (54%) reported that they definitely or Evaluates the coordinated response in development of unplanned care services for mental health (8) Identifies confidence and preparation of community mental health nurses when performing expanded roles (9) Identifies cultural factors that contributed to substance abuse in adolescents (10) Explores how mental health workers and respond to women who reveals sexual abuse in the scenario of crisis service (11) Professionals identify cultural barriers of women in attendance (11) Managing and negotiating health care delivery systems nurse practitioner-patient relationship teaching/coaching Function Analyzes the extent of mental health services provided to families (12) On the significance of the relationship with the patient, highlights the genuine partnership and confidence (13) Unidentified probably felt confident to prescribe medication. More than 90% said they probably or definitely felt confident in making recommendations for involuntary treatment, 84% and 79% showed similar levels of confidence in ordering of diagnostic tests and in referring patients to specialist physicians, respectively (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluated the extent to which professionals of community mental health programs provides services to families of people with severe mental illness and it was indicated that the overall level of services provided to families was very low. The less frequently services reported were: provide family therapy (2.4%), learning to identify early warning signs of relapse (9.5%), include the family in planning the client`s treatment (10.5% ), teaching methods to monitor medications (10.8%) and refer to family support group (11.9%) (12) . In this sense, the competence in the managing and negotiating health care delivery systems domain was not satisfactory because it advocates the provision of care for individuals, families and communities within the integrated health care services (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPs need information, education, support, practical advice on managing the illness, and someone to listen to them (Gavois, Paulsson, Fridund, 2006;Jakobsen & Severinsson, 2006;Jubb & Shanley, 2002;Kim & Salyers, 2008;Marshall & Solomon, 2000;McAuliffe et al, 2009;Rose, 1998;Smith, 2003).…”
Section: Background Literaturementioning
confidence: 99%
“…Studies conducted on caregivers of chronic mental ill patients indicate that people with mental illness are often looked after by their parents and supported very poorly by official health care services [15][16][17]. The continuity of care for individuals with chronic mental illness in the community depends on the ability of families to provide this care in a big way.…”
mentioning
confidence: 99%